2017
DOI: 10.4236/tel.2017.75088
|View full text |Cite
|
Sign up to set email alerts
|

Corruption and Economic Growth: The Case of EMCCA

Abstract: This article analyzes the relationship between corruption and economic growth in the countries of the Economic and Monetary Community of Central Africa (EMCCA). To our knowledge, there are no works dealing with the direct relations between the two variables in such a framework. For this purpose, we use panel data econometrics to show that over the period 2005 to 2015, corruption has favored economic growth in the CEMAC member countries by "grazing" the administrative burdens that impede access basic public ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 33 publications
(41 reference statements)
0
20
3
2
Order By: Relevance
“…However, those opposing this view noted that the greasing effect of corruption is only possible as a second best option in a bad institutional setting (Campos & Dimova, 2010). It is contrary to the result obtained by Boussalham (2018) and Tidiane (2019, Ondo (2017), Grindler et al (2019 and Bitterhout (2020) who found inverse relationship between corruption and economic growth.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…However, those opposing this view noted that the greasing effect of corruption is only possible as a second best option in a bad institutional setting (Campos & Dimova, 2010). It is contrary to the result obtained by Boussalham (2018) and Tidiane (2019, Ondo (2017), Grindler et al (2019 and Bitterhout (2020) who found inverse relationship between corruption and economic growth.…”
Section: Resultsmentioning
confidence: 59%
“…They further found that investment, population, democracy freedom and economic freedom have direct impact on economic growth. Ondo (2017) considered the relationship between corruption and economic growth in the Economic and Monetary Community of Central Africa and data within the period 2005 to 2015.They found that corruption, civil liberty, human capital and public spending have inverse relationship with economic growth in the community while private investment and commercial opening have positive relationship with economic growth. While civil liberty and private investment were significant at 1% level of significance, corruption was significant at 10% level of significance and noted that corruption may have a non-linear effect on economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…In response to one unit improvement in economic freedom, there is a statistically significant impact of 27% on fraud, again 27% in the case of an increase in poverty (Bosco 2016 found also a positive relation), a negative 90% in response to political stability (most studies identified a negative relationship, such as Nur-tegin and Czap 2012; Schumacher 2013; Turedi and Altiner 2016), 69% in the case of type of government (Achim et al 2018), a huge 20% in the case of inflation (positive relation between inflation and corruption or fraud was also found by Al-Marhubi 2000;Ata and Arvas 2011;Turedi and Altiner 2016;Omidi et al 2017), 20% in the case of gross domestic product, and 9% in the case of business operational risk (this relation was also obtained by Saha and Gounder 2013;Wang 2016;Ondo 2017).…”
Section: Fixed Effect Model I Fixed Effect Model-cs Fixed Dummy Variablesmentioning
confidence: 80%
“…Moreover, in an adverse economic environment, fraudulent activities are likely to increase, as in a recession people's income decreases and companies' financial resources for managing and investigating fraud are scarce (Gill 2011). However, some research has provided empirical support for a positive relation between these two indicators, particularly for developing economies (Saha and Gounder 2013;Wang 2016;Ondo 2017). The countries with a higher GDP are less corrupt than those with a lower GDP, but countries with a medium level of GDP are identified to be more corrupt than nations with a lower level of GDP (Saha and Gounder 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…investigates the relationship between corruption and economic development in 13 Asia-Pacific countries and observes that South Korea and China are record progress in economic advancement despite the rise in corruption cases Jiang and Nie (2014). also report China's miracle of progressive economic growth despite the increasing trend of corruption Ondo (2017). investigates the relationship between corruption and economic growth in the member countries of the Economic and Monetary Community of Central Africa (EMCCA).…”
mentioning
confidence: 99%